In Vitro Proliferation Of Porang Shoots (Amorphophallus muelleri Blume) In Several Combinations Of Bap And Tdz - Rahmadyah Hamiranti; Lisa Erfa; Nanang Wahyu Prajaka; Desi Maulida; Yuriansyah Yuriansyah (Jurnal Penelitian Pertanian Terapan, 2025)
Tissue culture can be used as an alternative technique that can be used to multiply porang seeds to meet the need for seeds in porang development. This study aims to determine the proliferation response of porang in various types and concentrations of BAP or TDZ. The experiment was carried out using a randomized block design (RAK). The treatments tried in the shoot proliferation experiment were P1 (MS 0), P2 (BAP 0.5 mg.l-1), P3 (BAP 1 mg.l-1), P4 (TDZ 0.5 mg.l-1) and P5 (TDZ 1 mg.l-1). Each treatment was tried with 5 replications, and each treatment per replication was planted with 5 bottles. Data were analyzed by Analysis of Variance, and differences between treatments were seen by the LSD test at the 5% level. The use of MS 0 and BAP 1 mg.l-1 gave better results compared to other treatments. The use of MS 0 and BAP 1 mg.l-1 resulted in 100% shoot growth on porang propagules. MS 0 and BAP 1 mg.l-1 produced the highest number of shoots (17.8 and 17.4) and the highest shoot height (3.52 and 2.50) compared to the other three treatments.